Waiting for "Superman" - Guggenheim, Davis; Kimball, Billy; Chilcott, Lesley; Strickland, Bill, 1947-; Canada, Geoffrey; Rhee, Michelle; Weingarten, Randi; Roland, Erich; Richman, Bob; Finton, Greg.; Cassidy, Jay.; Roberts, Kim; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2011)
"Provides an engaging and inspiring look at public education in the United States. [This documentary] has helped launch a movement to achieve a real and lasting change through the compelling stories of five unforgettable students such as Emily, a Silicon Valley eighth-grader who is afraid of being labeled as unfit for college, and Francisco, a Bronx first-grader whose mom will do anything to give him a shot at a better life."--container.
Special features: Optional audio feature commentary by director Davis Guggenheim and producer Lesley Chilcott -- Changing the odds (ca. 6 min. ; a look at innovative programs that are changing public education) -- Updates (text feature listing changes which have taken place since the making of the film) -- A conversation with Davis Guggenheim -- The future is in our classrooms -- The making of "Shine" (the film's title track by musician John Legend) -- deleted scenes.
DVD ; NTSC, Region 1 ; widescreen presentation ; Dolby Digital 5.1.
English or Spanish dialogue with optional English, French or Spanish subtitles ; closed-captioned.
Bill Strickland, Geoffrey Canada, Michelle Rhee, Randi Weingarten.
Cinematography by Erich Roland, Bob Richman ; edited by Greg Finton, Jay Cassidy, Kim Roberts ; music by Christophe Beck ; title track "Shine" written and performed by John Legend.
Companion book: Waiting for "Superman" : how we can save America's failing public schools / edited by Karl Weber.
Special features: Optional audio feature commentary by director Davis Guggenheim and producer Lesley Chilcott -- Changing the odds (ca. 6 min. ; a look at innovative programs that are changing public education) -- Updates (text feature listing changes which have taken place since the making of the film) -- A conversation with Davis Guggenheim -- The future is in our classrooms -- The making of "Shine" (the film's title track by musician John Legend) -- deleted scenes.
Keywords: Educational accountability -- Law and legislation -- United States; Education -- Standards -- United States; Education -- United States -- Evaluation; School improvement programs -- United States; Educational equalization -- United States; Public schools -- United States; z -- idex; Documentary films; Nonfiction films; Educational films; Feature films; Film adaptations; Video recordings for the hearing impaired